Your Place in the World - Relative Income and Global Inequality - Dietmar Fehr; Johanna Mollerstrom; Ricardo Perez-Truglia (Center for Economic Studies and Ifo Institute (CESifo), 2021)
There is abundant evidence on individual preferences for policies that reduce national inequality, but only little evidence on preferences for policies addressing global inequality. To investigate the latter, we conduct a two-year, face-to-face survey experiment on a representative sample of Germans. We measure how individuals form perceptions of their ranks in the national and global income distributions, and how those perceptions relate to their national and global policy preferences. We find that Germans systematically underestimate their true place in the world's income distribution, but that correcting those misperceptions does not affect their support for policies related to global inequality.
Keywords: C83; C91; D63; D72; H23; H24; 330; (global) inequality; redistribution; survey; experiment